The effect of stents structural parameters to flow in stented aneurysms - Mahat, Mohamad Mazwan (2008)
Investigation on the changes of flow patterns in a blood vessel with a fixed fusiform aneurysm resulting from placement of a different structural void area of stents. The velocity profile and pressure distribution after installing the device had been identified from the selected stent. Three different commercial stent designs were taken into consideration and these models will be referred to as type I, type II and type III. To identify the changes in local hemodynamics due to stent implantation, a stented and non stented aneurysm model was taken into considerations. The simulation of the model was studied under incompressible, Newtonian, viscous, non pulsatile condition in which we investigated computationally in a three-dimensional configuration using a fluid dynamics program. Hence, the different of stent structural pattern produces the different results of flow field around the stented aneurysm. The minimum velocity had improved after stents insertion and the type III with less void area results most optimized. However, the flow in stented fusiform aneurysms is very different from that in stented saccular aneurysms resulting lowest peak pressure 340 Pa which due to placement of stent type II. Finally, the correlations obtained from this numerical result could be used to investigate the pressure distribution around the diseased segment.